Integration of Islamic Education And Science: A Study On Pig Cornea Transplantation Based On Al-Shatiby's Perspective - Zaldi Zaldi; Asmuni Asmuni; Dhiauddin Tanjung (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research focuses on seeing how the integration between Islamic education and science, by looking at the case of pig eye cornea transplantation based on Al-Shatiby's perspective. Islamic education is important to adjust Islamic law as a guide for every Muslim to be a reference in carrying out all the activities of his life both his relationship with Allah and his relationship with fellow human beings even towards himself and other creatures. The development of medical technology today requires health experts to transplant / replace human eye corneas that experience blindness due to corneal abnormalities to be overcome while corneal donors derived from human eye corneas are very rare to obtain, one of which is due to the unwillingness of humans to become corneal donors, so doctors replace human eye corneas that experience corneal blindness with corneas derived from pigs that have been genetically engineered.  Islamic law comes from the Quran and the Sunnah of the Prophet, but if no clear text is found in a problem faced by humans, the scholars make ijtihad to determine the law through Ijmak and Qiyas. With the development of technology today, not all problems can be answered from existing sources and arguments of Islamic law, so other legal arguments are needed, such as Maslahah Mursalah. This also requires Islamic education in the medical field, so that patients and families understand the problems that exist, and understand the medical process. The integration of Islamic education in science, especially in the context of medical science can encourage the determination of Islamic law on pig corneal transplants as a substitute for human corneas, especially by using the Maslahah Mursalah Theory approach from Imam Al-Shatiby.